The social archaeology of Australian indigenous societies - David, Bruno, 1962-; Barker, Bryce; McNiven, Ian.; Australian Institute of Aboriginal and Torres Strait Islander Studies (Canberra, A.C.T. : Aboriginal Studies Press, 2006)
Reveals the ancient past of Aboriginal Australians to be one of long term changes in social relationships and traditions, as well as the active management and manipulation of the environment.
Includes index.
"Aboriginal Studies Press is the publishing arm of Australian Institute of Aboriginal and Torres Strait Island Studies".
Bibliography: p. 322-367.
Keywords: Aboriginal Australians -- Social life and customs; Social archaeology -- Australia; Archaeology - Theory and criticism; Yanyuwa / Yanuwa people (N153) (NT SE53-04); Anthropology; Social organisation; Archaeology - Intensification; Technology - Stone; Plants - Cycads; Archaeology; Material culture; Australia -- Antiquities; Western Desert (WA SF51, SF52, SG51, SG52); Roonka (SE SA SI54-10); Lake Surprise (SW Vic SJ54-07); Badu / Mulgrave Island (Qld TSI SC54-11); Torres Strait Islands (Qld TSI SC54, SC55-05)